The Importance of Personalized Learning: How to Tailor Education to the Individual Needs of Students - Cittra Juniarni; M. Ali Sodikin; Akhyar Akhyar; Almujahid Almujahid; Nova Asvio (Education Studies and Teaching Journal (EDUTECH), 2024)
Personalized learning has become a major concern in educational research because of its potential to improve student learning outcomes. This research aims to evaluate the effectiveness of various personalized learning approaches in improving student learning outcomes. The method used is a systematic literature review which includes analysis of articles from highly reputable databases such as Scopus, Web of Science, and PubMed. Research results show that approaches such as adaptive learning systems, competency-based learning, and differentiated instruction can increase student engagement, motivation, and academic achievement. The study also found that factors such as student characteristics, learning context, and learning program design influence the success of personalized learning. The implication of this research is the need to develop more flexible and adaptive learning strategies as well as increase technological support to optimize student learning outcomes.